Investigation of rotational augmentation mechanisms on wind turbine blade sections based on Quasi-3D simulations - Rodrigues, Pedro [UNESP]; Gennaro, Elmer Mateus; Souza, Daniel [UNESP] (Springer Nature, 2025)
Rotation has been recognized for its ability to decrease the extent of separate flow regions on the inner sections of horizontal-axis wind turbine blades. This alteration is often linked to centrifugal pumping. Nevertheless, studies focused on insect flight conditions revealed a significant contribution of the Coriolis acceleration to the balance of vorticity within the leading-edge vortex (LEV). Despite this insight, it remains unexplored whether this phenomenon contributes to the observed rotational augmentation in wind turbines. Our study employed quasi-3D simulations to delve into the impact of Coriolis acceleration on the balance of span-wise vorticity within the region of separate flow along the upper surface of wind turbine blade sections. Our results allowed the identification of two different mechanisms of rotational augmentation, one associated to the height reduction of the region of separate flow and the other associated to the stabilization of the LEV. The former occurred when a trailing-edge separation was observed and the later when the flow featured a leading-edge separation. Within the range of conditions considered, the Coriolis acceleration neutralized up to about 40% of the span-wise vorticity flowing in from the boundary layer to feed the LEV.